Application of chlorous acid water for disinfection of surgical site in dairy cows - Ichii, Osamu; Nakamura, Teppei; Hiraishi, Masaya; Namba, Takashi; Rubel, Md. Zahir Uddin; Umeyama, Takuya; Asai, Megumi (Frontiers in Veterinary Science, 2025)
Disinfection is crucial for preventing surgical site infections. Recently, the effectiveness of sanitizers using chlorous acid (HClO2) under conditions rich in organic matter has been reported, and chlorous acid water (CAW) has been approved as a food additive. This study evaluated the potential of CAW as a new presurgical disinfectant for cattle. The experiments were performed on the paralumbar fossa of cattle in Sapporo during March (winter to spring) and August (summer). Colony-forming units (CFUs) of standard plate count bacteria (SPCB), Enterococcus faecalis (EF), Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus spp. (SP) were analyzed as indicators of bacterial load. SPCB and SP were abundantly detected, exceeding 6 log10 CFU/100 g on clipped hair and 6 log10 CFU/100 cm2 on the skin immediately after clipping, with no significant seasonal differences. The bacterial load on the skin was evaluated at three time points: after clipping, cleansing, and disinfection. Clipping and cleansing with liquid soap were common procedures, following this, either the standard disinfection protocol using 7.5% iodine scrub for 1 min, 10% povidone-iodine for 5 min, and 70% alcohol for 5 min (SPA), or a modified protocol using CAW with contact times of 15, 10, or 5 min (CAW15, CAW10, CAW5) were performed separately. The cleansing procedure significantly reduced the SPCB, EF, and SP on the skin after clipping, and all disinfection methods significantly decreased the SP after cleansing. Draping significantly enhanced the disinfection efficiency of the SPA, CAW10, and CAW5 protocols. The CAW procedure did not alter skin histology in the paralumbar fossa or udder compared to 10% povidone-iodine or 70% alcohol. Our data suggest that the disinfection method using CAW is useful and comparable to routine disinfection methods and might reduce the time required for presurgical disinfection in farm fields.